2021
DOI: 10.1111/nph.17621
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric epigenetic modification and homoeolog expression bias in the establishment and evolution of allopolyploid Brassica napus

Abstract: Summary This study explores how allopolyploidization reshapes the biased expression and asymmetric epigenetic modification of homoeologous gene pairs, and examines the regulation types and epigenetic basis of expression bias. We analyzed the gene expression and four epigenetic modifications (DNA methylation, H3K4me3, H3K27me3 and H3K27ac) of 29 976 homoeologous gene pairs in resynthesized, natural allopolyploid Brassica napus and an in silico ‘hybrid’. We comprehensively elucidated the biased gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 62 publications
(99 reference statements)
1
27
0
Order By: Relevance
“…Our results showed that approximately 64 million ( B. rapa , A2) to 102 million ( B. oleracea , C2) raw reads were obtained from ATAC-Seq, more than 96% of which were clean reads in all samples (Table S1 ). According to previous studies 38 , 40 , we constructed an in silico ‘hybrid’ (A_C), which can fuse well with parental data for the convenience of subsequent studies, by mixing the reads of B. rapa and B. oleracea in equal proportions. As shown in Table S1 , an average of approximately 94.7%, 95.6%, 93.0%, and 98.0% of clean reads from the ATAC-Seq data of B. rapa , B. oleracea , resynthesized B. napus , and natural B. napus were mapped to the genome of B. napus 35 , and the GC content of each sample was higher than 40%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results showed that approximately 64 million ( B. rapa , A2) to 102 million ( B. oleracea , C2) raw reads were obtained from ATAC-Seq, more than 96% of which were clean reads in all samples (Table S1 ). According to previous studies 38 , 40 , we constructed an in silico ‘hybrid’ (A_C), which can fuse well with parental data for the convenience of subsequent studies, by mixing the reads of B. rapa and B. oleracea in equal proportions. As shown in Table S1 , an average of approximately 94.7%, 95.6%, 93.0%, and 98.0% of clean reads from the ATAC-Seq data of B. rapa , B. oleracea , resynthesized B. napus , and natural B. napus were mapped to the genome of B. napus 35 , and the GC content of each sample was higher than 40%.…”
Section: Resultsmentioning
confidence: 99%
“…14b–d and 17 ). To further explore the cause of the differences between the two subgenomes, we divided the genes of each genotype into homeologous genes and subgenome-unique genes according to our previous study 38 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tauschii (~5.5 MYA) (Glémin et al, 2019 ) and between far source parents of allopolyploids (Shi et al, 2012 ), which enabled the accumulation of genetic variations in cis elements, such as promoters, enhancers, and gene bodies. Additionally, recent studies in wheat and Brassica have suggested subgenome-specific epigenetic modifications are also key factors regulating homoeolog expression bias (Li M. et al, 2021 ; Wang et al, 2021 ); however, those latter factors still need further validation in multiple tissues or at different developmental stages in synthesis and natural allopolyploid systems. Notably, despite its prevalence among HSE patterns, the cis -only pattern was not particularly conserved among tissues, suggesting that trans effects, especially tissue-specific trans effects, may balance expression differences between homoeolog mates and play a further fine-tuning role in HSE regulation.…”
Section: Discussionmentioning
confidence: 99%